THE IMPACT OF LEARNING ORIENTATION ON FINANCIAL PERFORMANCE WITH NON-FINANCIAL PERFORMANCE AS A MEDIATING VARIABLE - vicky F sanjaya (Universitas Teknokrat Indonesia, 2018)
This study aims to see the impact of learning orientation on the performance of companies in financial and non-financial, and see the role of non-financial performance as a mediating variable. No relevant profit theory and still limited research that saw the company's performance from both sides of the financial and non-financial to be a gap for doing research. The sample in this study is small and medium enterprises (SMEs) domiciled in the Province of Yogyakarta (DIY). The number of samples studied is as many as 113 respondents consisting of five districts / cities in DIY. The results of this study indicate that the orientation of learning has a positive and significant impact on financial performance and non-financial companies. In addition, this study also gives results that non-financial performance mediates some of the relationship between learning orientation to financial performance.Keywords: learning orientation, financial performance, non-financial performance, SMEs.